Revivifying the Ius Commune - Osvaldo Cavallar; Julius Kirshner (Reti Medievali Rivista, 2021)
Starting from and building upon the perceptive readings and careful contextualization of Jurists and Jurisprudence in Medieval Italy: Texts and Contexts by our four discussants, our reply centers on the institutional setting for which our collection of translations was initially intended: the classroom. Fully aware that classrooms and academic curricula are not the same around the world, we revert to the two questions that were constantly at the back of our minds while assembling the volume: why teach the ius commune and how to go about it? To these two questions, one might add a third one: what are the rewards of such a challenging enterprise? The first section recapitulates the rationale for the unconventional nature of our work; the second fragments the whole into sections, exemplifying how the texts were used in a socioeconomically and ethnically diverse classroom in the highly decentralized system of higher education in the U.S. that brought together students from different academic departments; the third, exiting the anglophone world, illustrates the reactions to the translations of an international group of students in Japan.